Opportunities And Challenges of Indian Corporates in the Adoption of Benchmarking Strategy - Jaffar, Mohamed (Quest Journals, 2025)
In the face of intensifying global competition and evolving customer expectations, Indian corporate entities are increasingly turning to benchmarking as a strategic tool for performance enhancement and innovation. Benchmarking enables organisations to evaluate their practices against industry leaders, adopt best-in-class methods, and drive continuous improvement across operational, financial, and strategic domains. This article provides a comprehensive overview of benchmarking, explores various methodologies, and analyses the key opportunities it presents, ranging from operational efficiency to customer satisfaction and innovation. Simultaneously, it discusses the inherent challenges, including data accessibility, cultural differences, organisational resistance, and resource limitations. By critically examining these dimensions, the article aims to guide Indian corporates in leveraging benchmarking for sustainable competitive advantage and long-term growth.
ISME
Keywords: Benchmarking; Indian corporates; best practices; operational efficiency; competitive strategy; innovation; performance improvement; strategic management; global competitiveness; continuous improvement